Anti-hepatotoxic prospect of Panax Ginseng extract and/or Selenium against D-galactosamine-induced liver injury in experimental rats - Almajwal, Ali; Elsadek, Mohamed Farouk (Progress in Nutrition, 2014)
The present study was performed to examine hepatoprotective effect of White Panax Ginseng ethanol extract (WPGE) and/or Selenium (Sel) against D-galactosamine-induced liver injury in rats. The rats received a single dose of D-Galactosamine (D-GalN) (200 mg/kg, i.p) one day before sacrifice to induce hepatotoxicity; the ethanol extract of White Panax Ginseng (240 mg/kg body weight), Selenium (0.4 mg/Kg body weight) individually and combination of (WPGE + Sel) were administered for 6 weeks. It was found that D-GalN induced hepatic damage resulted in a significant increase in the activity of AST, ALT and ALP. Results also showed that increased levels of serum cholesterol, triglycerides, low density lipoprotein (LDL-C) and very low density lipoprotein (VLDL-C) while decreased level of high density lipoprotein (HDL-C) in D-GalN induced rats. In addition the antioxidant activities such as reduced glutathione (GSH), vitamin E, superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GPx) were decreased in D-GalNinduced rats’ tissues.WPGE and Sel individually and combination (WPGE + Sel) treatments attenuated the abnormal lipid metabolism, increased oxidative stress, reduced antioxidants and also having protective activity against D-GalN induced hepatotoxicity in rats especially for the (WPGE + Sel) combined group which reveﾭaled the best results of all treatments. Thus the present study provides a scientific rationale for the traditional use of this plant extract and Sel in the management of liver diseases.